2020
DOI: 10.1108/jima-06-2020-0172
|View full text |Cite
|
Sign up to set email alerts
|

Non-Muslim consumers’ intention to purchase halal food products in Malaysia

Abstract: Purpose This study aims to identify the intention to purchase Halal food products amongst non-Muslim consumers in Malaysia, moderated by the acculturation effect. Design/methodology/approach A structured close-ended questionnaire was used to gather data through the random distribution of 397 non-Muslim consumers from the Alumni network of several private higher education institutions in Malaysia. Findings The collected data was analyzed through the structural equation modelling technique using partial leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 72 publications
0
34
0
5
Order By: Relevance
“…The questionnaire was designed in a statement format and then tested for descriptive analysis and confirmatory factor analysis (CFA) structural equation modelling (SEM). The confirmatory factor analysis (CFA) and structural equation modelling (SEM) were analyzed by IBM Amos 22 software (Lim et al, 2020).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire was designed in a statement format and then tested for descriptive analysis and confirmatory factor analysis (CFA) structural equation modelling (SEM). The confirmatory factor analysis (CFA) and structural equation modelling (SEM) were analyzed by IBM Amos 22 software (Lim et al, 2020).…”
Section: Data Collectionmentioning
confidence: 99%
“…As a result, the global halal market has been expanded in the last few years with halal food products recording $632 billion sales, which is equivalent to 16% of the entire global food industry (Izberk-Bilgin and Nakata, 2016). It is not surprising since healthrelated quality is one of the main determinants of food quality dimensions (Lim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPB has been applied widely and successfully in many studies as a theoretical framework from which to examine the purchase intention in halal food consumption (Amalia et al, 2020;Lim at al., 2020;Marmaya at al., 2019), organic food consumption (James et al, 2019;Mohammed, 2020;Teng & Wang, 2015), functional food consumption (Xin & Seo, 2019), genetically modified food consumption (Rabbanee et al, 2020;Zheng et al, 2017;Zhu et al, 2018), green food consumption (Amin & Tarun, 2020), ethnic food consumption (Ahmad et al, 2019) and counterfeit products (Fernandes, 2013). Hence, the TPB model is deemed suitable as the theoretical foundation for this research to understand honey buyers' purchase intention.…”
Section: Theoretical Framework -Theory In Support Of Intention To Purchasementioning
confidence: 99%
“…Various studies have examined and shown the positive influence of halal awareness and its implications on behavioral intention [1,4,5]. Conversely, some studies show that halal awareness does not influence behavioral intention [6].…”
Section: Introductionmentioning
confidence: 99%